Nutrient sources and their application in cassava cultivation - Howeler, Reinhardt H. (Burleigh Dodds Science Publishing Limited, 2017)
This chapter discusses various sources of nutrients to be applied to prevent soil nutrient depletion, as well as the optimum rates, times and methods of their application. It also describes how computer models can predict site-specific nutrient requirements and balanced fertilizer rates to maximize nutrient use efficiency, increase farmers’ profits and prevent waste and potential pollution of the environment. It ends by considering the variation among cassava genetic resources in nutrient use efficiency in order to breed new varieties with greater tolerance to low soil fertility.